2018
DOI: 10.3892/etm.2018.6542
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibition of RKIP aggravates thioacetamide‑induced acute liver failure in mice

Abstract: Accumulating evidence has indicated that Raf kinase inhibitor protein (RKIP) is involved in several intracellular signaling pathways; its abnormal expression is associated with tumor progression and metastasis in several human neoplasms. However, the role of RKIP in acute liver injury has remained elusive. In the present study, acute liver failure was induced by thioacetamide in mice, and locostatin was used to interfere with RKIP expression. It was found that RKIP expression was significantly inhibited by loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…TAA-induced hepatic inflammation, fibrosis, and liver damage in mice, in terms of clinical features, are very close to chronic human liver disease [ 11 ]. After TAA exposure, the levels of plasma alanine aminotransferase (ALT) and aspartate aminotransferase (AST) are upregulated due to hepatocyte membrane damage, which causes a leakage of transaminase enzymes into the systemic circulation [ 12 ]. The advantage of using the TAA model for the hepatotoxin animal model is its unique specificity for targeting the liver [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TAA-induced hepatic inflammation, fibrosis, and liver damage in mice, in terms of clinical features, are very close to chronic human liver disease [ 11 ]. After TAA exposure, the levels of plasma alanine aminotransferase (ALT) and aspartate aminotransferase (AST) are upregulated due to hepatocyte membrane damage, which causes a leakage of transaminase enzymes into the systemic circulation [ 12 ]. The advantage of using the TAA model for the hepatotoxin animal model is its unique specificity for targeting the liver [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…After TAA exposure, the levels of plasma alanine aminotransferase (ALT) and aspartate aminotransferase (AST) are upregulated due to hepatocyte membrane damage, which causes a leakage of transaminase enzymes into the systemic circulation [ 12 ]. The advantage of using the TAA model for the hepatotoxin animal model is its unique specificity for targeting the liver [ 12 , 13 ]. The toxicity is because of its bioactivation led by a mixed-function oxidase system—mainly, the cytochrome P2E1 and flavin adenine dinucleotide monooxygenases [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic inflammation is common in liver injury associated with liver fibrosis, cirrhosis, and HCC. Promising anti-inflammatory molecules can be considered a cornerstone of liver disease treatment [ 17 ]. Many studies have demonstrated that SSd has beneficial effects on health via anti-inflammatory, antioxidant, neuroprotective, anticancer, and cardioprotective activities [ 28 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…The biochemical processing of TAA within the cellular milieu leads to oxidative damage of hepatocytes, which in turn causes degeneration and necrosis in liver tissue [ 16 ]. TAA-induced hepatic inflammation, fibrosis, and liver damage in mice are, in terms of clinical features, comparable to chronic liver disease in humans [ 10 , 17 ]. Accordingly, the advantage of using TAA to induce hepatoxicity in animal models is its unique specificity in targeting the liver [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation